Embracing the complexity: a multifaceted and inter-sectional model of Taught Postgraduate student experience. Issue 10 (26th November 2021) - White, Wendee; Ingram, Richard
ABSTRACT: Postgraduate taught student experience (PGT) is the product of a complex journey. During study, PGT students face an array of emotions and stressors associated with biopsychosocial-cultural processes interacting in, across, and in response to various dynamic systems that serve to threaten or challenge their study journey, making wellbeing an important factor in their experience. This paper unfolds and examines the utility of an integrated model for exploring, understanding, and responding to student experience according to these interacting processes and dynamic systems. Using an integrated framework, we conceptualise student experience as a transactional process arrived at through person–environment interactions informed by the synergistic effect of biopsychosocial-cultural processes, emotion responses, and wellbeing. We use a meta-appraisal approach to explore the intra and interpersonal processes that inform PGT student interactions in and across the complex systems of higher education and the role of the student as an active participant within their own eco-system. This approach is appealing as it engages multiple perspectives, exploring the individual according to four intersecting, ontological dimensions: mind, body, culture, society and overcoming any ontological or epistemological priorities assigned through a reductionist lens. Through this multifaceted conception we propose new potential for enacting practices and contexts to actualise the transformative potentials of higher education to support sustainable development.